Evaluation of Patient Reported Safety and Efficacy of Cannabis From a Survey of Medical Cannabis Patients in Canada - Cahill, Shaina P.; Lunn, Stephanie E.; Diaz, Patrick; Page, Jonathan E. (Frontiers in Public Health, 2021)
With the medical use of cannabis permitted in Canada since 2001, patients seek to use this botanical drug to treat a range of medical conditions. However, many healthcare practitioners express the need for further scientific evidence around the use of medical cannabis. This real-world evidence study aimed to address the paucity of scientific data by surveying newly registered medical cannabis patients, before beginning medical cannabis treatment, and at one follow up 6 weeks after beginning medical cannabis treatment. The goal was to collect data on efficacy, safety and cannabis product type information to capture the potential impact medical cannabis had on patient-reported quality of life (QOL) and several medical conditions over a 6-week period using validated questionnaires. The 214 participants were mainly male (58%) and 57% of the population was older than 50. The most frequently reported medical conditions were recurrent pain, post-traumatic stress disorder (PTSD), anxiety, sleep disorders [including restless leg syndrome (RLS)], and arthritis and other rheumatic disorders. Here we report that over 60% of our medical cannabis cohort self-reported improvements in their medical conditions. With the use of validated surveys, we found significant improvements in recurrent pain, PTSD, and sleep disorders after 6 weeks of medical cannabis treatment. Our findings from patients who reported arthritis and other rheumatic disorders are complex, showing improvements in pain and global activity sub-scores, but not overall changes in validated survey scores. We also report that patients who stated anxiety as their main medical condition did not experience significant changes in their anxiety after 6 weeks of cannabis treatment, though there were QOL improvements. While these results show that patients find cannabis treatment effective for a broad range of medical conditions, cannabis was not a remedy for all the conditions investigated. Thus, there is a need for future clinical research to support the findings we have reported. Additionally, while real-world evidence has not historically been utilized by regulatory bodies, we suggest changes in public policy surrounding cannabis should occur to reflect patient reported efficacy of cannabis from real-world studies due to the uniqueness of medical cannabis's path to legalization.